Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T19:57:33+01:00
A)
2x-y=5
-y=5-2x /*(-1)
y=-5+2x

b)
1/3y=x-3
y=3x-9

c)
3(x-y)=2x
3x-3y=2x
-3y=2x-3x
-3y=-x /*(-1)
3y=x
y=1/3 x

d)
2/3x=3/4y
y=2/3x*4/3
y=8/9x

e)
4x+2y=1
2y=1-4x
y=1/2 -2x

f)
6x- 2/3y=2
- 2/3y=2-6x /*(-1)
2/3y=6x-2
y=9x-3
2009-12-02T20:01:26+01:00
A) 2x-y=5 |-2x
-y=5-2x |*(-1)
y=-5+2x

b) 1/3y=x-3 |*3
y=3x-9

c) 3(x-y)=2x
3x-3y=2x |-3x
-3y=2x-3x |:(-3)
y= -2/3x + x
y= 1/3x

d)2/3x=3/4y |*4/3
2/3x*4/3=y
y= 8/9x

e)4x+2y=1 |-4x
2y=1-4x |:2
y= 1/2 - 2x

f) 6x- 2/3y=2
- 2/3y=2-6x |*(-1)
2/3y=6x-2
y=9x-3